(untitled) (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2021)
This research had the objective to measure the effectiveness of ASSURE teaching model in the integration of technology and learning media in the process of virtual-based English learning. One class comprising of 20 students of 6th grade was chosen as the sample of this study. A quantitative descriptive method was applied by using both pre-and post-tests as the instruments in collecting the data. In analyzing the data, the average score difference gained by the students in these two tests was firstly measured before they were further calculated through the ’Paired sample t-test’. The analysis revealed that the mean score reached by the students in the post-test (80.75) was higher than their performance in the pre-test (56). Additionally, the t-test score hit by these students was 14.14; bigger than the value of the t-table (1.73) in the significance level of 5% (0.05). This also explained that ASSURE teaching model as variable X significantly influenced students’ English achievement (variable Y). These findings confirmed that in the integration of technology and learning media in English virtual instruction, ASSURE teaching model was effective in increasing students’ English achievements.